Hormonal and electrolyte predictors for methotrexate versus surgery in ectopic pregnancy - Yusuf Başkıran; Kazım Uçkan; İzzet Çeleğen; Fatma Başak Tanoğlu (PLoS ONE, 2025)
This retrospective study investigates the association between maternal serum electrolyte and hormone levels and the success of methotrexate (MTX) treatment in ectopic pregnancies, aiming to identify predictive factors and improve clinical outcomes. A total of 372 patients treated with single-dose MTX between 2012 and 2023 were included, divided into two groups: those who successfully responded to MTX and those requiring surgical intervention. Significant differences were observed in beta-hCG levels, with a mean of 1376 in the MTX-successful group and 2358 in the surgical group. Electrolyte analysis showed that patients who responded successfully to MTX had higher potassium and albumin levels, whereas magnesium levels were lower compared to the surgical group. Haematological parameters also varied, with higher hemoglobin and hematocrit levels observed in the MTX-successful group. The findings suggest that serum potassium, magnesium, and albumin levels may be predictive markers for MTX efficacy. Higher potassium and albumin levels, along with lower magnesium levels, may contribute to improved treatment outcomes. These results support the potential role of dietary interventions—such as increasing potassium and albumin intake and moderating magnesium levels—in enhancing MTX success rates. This study underscores the importance of maternal biochemical profiles in guiding treatment strategies for ectopic pregnancy and highlights the value of individualized approaches to optimize outcomes and minimize the need for surgical intervention. Future research should aim to elucidate the biological mechanisms underlying these associations and validate the findings in larger and more diverse patient populations.